ANALISIS LOYALITAS MEREK KENDARAAN MITSUBISHI L300 - Yunada Arpan; B Brian Diaspri (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
This study was conducted to analyze the factors that affect consumers to develop theirloyalty. The independent variable of this study is brand trust, and the dependent variable is brandloyalty of Mitsubushi L300 vehicles on company PT. Lautan Berlian Utama Motor. Analysis used is asimple regression analysis, and the results is Y = 1,550 + 0,241 X1 + 0,345 X2 + 1,006 X3. Theindependent variables were the greatest influence on the dependent variable is a characteristic ofthe brand-customer relationship (5,025), followed by the variable characteristics of companies(2,149).Coefficient of determination (adjusted R2) is 0.899 means that the model koefesiensi greatdetermination. Based on the research results, suggestions can be given that the company needs tooptimize the application of these three variables.